2020
DOI: 10.3991/ijim.v14i05.13359
|View full text |Cite
|
Sign up to set email alerts
|

Early Investigation of the Impact of Mobile Learning Ethics Student-Generated Activities for STEM Subjects in a Local Malaysian University Context

Abstract: Mobile learning is fairly new in the local context, particularly for STEM subjects in Malaysia universities. However, this raises the issue of the ethics of mobile technology. With the advancement of mobile technologies few studies have been conducted for mobile ethics in student-generated activities. The aim of this research is to investigate the impact of mobile learning student-generated activities ethics in Malaysia. The methodology used in this research is largely qualitative with students from a local un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…13 The data was analysed using a thematic analysis approach, in which the data was analysed into codes, then categories, followed by themes. 14 The Standards for Reporting Qualitative Research: A Synthesis of Recommendations (SRQR) was a guide in reporting this study.…”
Section: Methodsmentioning
confidence: 99%
“…13 The data was analysed using a thematic analysis approach, in which the data was analysed into codes, then categories, followed by themes. 14 The Standards for Reporting Qualitative Research: A Synthesis of Recommendations (SRQR) was a guide in reporting this study.…”
Section: Methodsmentioning
confidence: 99%
“…PhET simulations are animated, user-friendly, and reminiscent of a game, enabling students to learn through hands-on experience. Students can easily comprehend the conceptual physical models presented in the simulations, which emphasize the user's transition between real-world events and mobile simulations [21]. Atoms, photons, electrons, and electric fields are some of the intangible elements that constitute PhET simulations.…”
Section: Mobile Simulationmentioning
confidence: 99%
“…The unprecedented expansion of wireless technologies and of their roles in people's lives has led to everincreasing interest among researchers. While initially many research projects, including our own [5,6], largely focused on social uses of mobile phones, investigations into the place of mobile phones in educational settings have been gaining momentum (e.g., see [3,[7][8][9][10][11][12]), ranging from students' attitudes toward them in Jordan [7], uses of them in lectures in Australia [8], and ethical concerns about them in Myanmar [9]. The global pandemic of 2020, which continues into 2021, forced many educational establishments out of traditional face-to-face and into online instructional environments.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, Godwin-Jones [13] observed that as smartphones became more affordable and pervasive, they came to be seen as important tools in mobile learning (mlearning). However, recent studies [10,14,15] have noted that mobile phones' uses in educational environments remain understudied. While researchers [16,17,18] remark that there is much to be learned about the effectiveness of small mobile technologies in education, educators and administrators raise concerns about the costs required to deploy and maintain such technologies and their reported negative effects (e.g., increasing instances of student cheating and distraction).…”
Section: Introductionmentioning
confidence: 99%